Synthesis of a novel DPPA‐containing benzoxazine to flame‐retard epoxy resin with maintained thermal properties. (9th May 2019) - Luo, Qinqin; Sun, Yulin; Yu, Biao; Li, Chengpeng; Song, Jiangli; Tan, Dexin; Zhao, Jianqing
Abstract : The flame‐retarded epoxy resin with improved thermal properties based on environmentally friendly flame retardants is vital for industrial application. Hereby, a novel reactive‐type halogen‐free flame retardant, 10‐(3‐(4‐hydroxy phenyl)‐3, 4‐dihydro‐2H‐benzo[e] [1, 3] oxazin‐4‐yl)‐5H‐phenophosphazinine 10‐oxide (DHA‐B) was synthesized via a two‐step reaction route. Its structure was characterized using 1 H, 13 C, and 31 P NMR and HRMS spectra. For 4, 4′‐diaminodipheny ethane (DDM) and diglycidyl ether of bisphenol A (DGEBA)‐cured systems, the epoxy resin with only 2 wt% loading of DHA‐B passed V‐0 rating of UL‐94 test. Significantly, its glass transition temperature ( T g ) and initial decomposition temperature ( T 5% ) were as high as 169.6°C and 359.6°C, respectively, which were even higher than those of the corresponding original epoxy resin. Besides, DHA‐B decreased the combustion intensity during combustion. The analysis of residues after combustion suggested that DHA‐B played an important role in the condensed phase.